PEMANFAATAN MEDIA SOSIAL TERHADAP FENOMENA â€œHOAXâ€ DI KALANGAN REMAJA MILENIAL (STUDI DI SMAN 1, KECAMATAN PLERET,BANTUL, YOGYAKARTA) - Dyaloka Puspita Ningrum (Universitas Widya Mataram, 2019)
Social media is the media of choice for information and communication used by todayâ€™s millennial generation, especially for participants in the service consisting of 2 nd grade students of SMA N 1 Pleret, Bantul, Yogyakarta. Much of the phenomenon of cybercrime is the spread of hoaxes that need high attention and alertness.this service activity was conducted using speech, discussion and simulation methods. The government is trying though theÂ UU ITE to prevent and reduce negative contentâ€™s in cyberspace with sanctions and threats legally that can harm others. Young people as a generation of the nation must be able to take smart and wise actions from existing social problems. Dissemination of hoax news in the form of SMS broadcasts, job carrier or information in the form of social events in the community without any clear source has occurred and has become a boomerang for media users themselves. There have been many parties responsible and dealing with the legal umbrella. As the nationâ€™s successor, millennial adolescents must increase socialization activities and fight hoaxes as crimes in cyberspace without having to trust every photo and video circulating in the public.